Oral fructose intake does not improve exercise, visual, or cognitive performance during acute normobaric hypoxia in healthy humans - Post, Titiaan E.; Schmitz, Jan; Denney, Cayla; De Gioannis, Riccardo; Weis, Henning; Pesta, Dominik; Peter, Andreas; Birkenfeld, Andreas L.; Haufe, Sven; Tegtbur, Uwe; Frings-Meuthen, Petra; Ewald, Ann C.; et al. (Frontiers in Nutrition, 2023)
Introduction The ability to metabolize fructose to bypass the glucose pathway in near-anaerobic conditions appears to contribute to the extreme hypoxia tolerance of the naked-mole rats. Therefore, we hypothesized that exogenous fructose could improve endurance capacity and cognitive performance in humans exposed to hypoxia. Methods In a randomized, double-blind, crossover study, 26 healthy adults (9 women, 17 men; 28.8 ± 8.1 (SD) years) ingested 75 g fructose, 82.5 g glucose, or placebo during acute hypoxia exposure (13% oxygen in a normobaric hypoxia chamber, corresponding to oxygen partial pressure at altitude of ~3,800 m) on separate days. We measured exercise duration, heart rate, SpO2, blood gasses, and perceived exertion during a 30-min incremental load test followed by Farnsworth-Munsell 100 Hue (FM-100) color vision testing and the unstable tracking task (UTT) to probe eye-hand coordination performance. Results Exercise duration in hypoxia was 21.13 ± 0.29 (SEM) min on fructose, 21.35 ± 0.29 min on glucose, and 21.35 ± 0.29 min on placebo (p = 0.86). Heart rate responses and perceived exertion did not differ between treatments. Total error score (TES) during the FM-100 was 47.1 ± 8.0 on fructose, 45.6 ± 7.6 on glucose and 53.3 ± 9.6 on placebo (p = 0.35) and root mean square error (RMSE) during the UTT was 15.1 ± 1.0, 15.1 ± 1.0 and 15.3 ± 0.9 (p = 0.87). Discussion We conclude that oral fructose intake in non-acclimatized healthy humans does not acutely improve exercise performance and cognitive performance during moderate hypoxia. Thus, hypoxia tolerance in naked mole-rats resulting from oxygen-conserving fructose utilization, cannot be easily reproduced in humans.